Pasteurella Multocida Bacteremia In Humans: A Clinical Report - Hendrie, John (1974)
Although Pasteurella multocida is a very common pathogen in animals, it has rarely been recognized as an infection of man. The first human infection was reported in 1913; between then and 1960 only 40 cases were reported in the world literature. The present patient became toxically ill following a bite from a domestic cat, and Pasteurella Multocida was grown on blood culture. The reason for the study is that the infecting agent can cause lesions in almost any body tissue, but up till now no report of liver involvement is available. Painful local inflammation after animal bites in humans deserves a search for Pasteurella multocida, which shows a sensitivity to penicillin unusual in a gram negative bacterium.